The role of hematologic parameters in recurrent aphthous stomatitis - Oner, Umran; Oner, Fatih; Kurt, Osman; Ozdemir, Sevki (Annals of Medical Research, 2021)
Aim: Recurrent Aphthous Stomatitis (RAS) is one of the most common diseases of oral mucosa characterized by recurrent painful ulcers. Although many factors have been implicated in the etiology of the disease, it has not yet been fully elucidated. We aimed to investigate serum vitamin B12, ferritin, folate, vitamin D, hemoglobin, and thyroid stimulating hormone (TSH) levels in patients with RAS.Materials and Methods: The study involved in 60 patients (34 women, 26 men) with idiopathic RAS and 70 healthy volunteers (41 women, 29 men). The serum vitamin B12, ferritin, folate, vitamin D, hemoglobin, and TSH levels of the patients were measured and statistically compared.Results: Serum levels of vitamin B12 (204.5 vs. 301.0 pg/ml) and ferritin (31.0 vs. 48.5 ml/ng) were significantly lower and serum level of folate (7.7 vs. 6.7 ng/ml) were significantly higher in the patient group than control group (p0.05). No correlations were detected between RAS assessed by family history, mean duration of disease, and frequency of attacks and hematinic deficiencies. Conclusion: Vitamin B12 and ferritin deficiency can play a role in the underlying etiology of RAS therefore we suggested the investigation of the vitamin B12 and ferritin status in RAS patients.
Keywords: Aphthous stomatitis; ferritin; folate; thyroid stimulating hormone; Vitamin Bsub12/sub; Vitamin D